Proceedings 2020 Network and Distributed System Security Symposium 2020
DOI: 10.14722/ndss.2020.24383
|View full text |Cite
|
Sign up to set email alerts
|

Carnus: Exploring the Privacy Threats of Browser Extension Fingerprinting

Abstract: With users becoming increasingly privacy-aware and browser vendors incorporating anti-tracking mechanisms, browser fingerprinting has garnered significant attention. Accordingly, prior work has proposed techniques for identifying browser extensions and using them as part of a device's fingerprint. While previous studies have demonstrated how extensions can be detected through their web accessible resources, there exists a significant gap regarding techniques that indirectly detect extensions through behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…On the other hand, using a randomized value will result in the website calculating different identifiers across visits. As such, websites can leverage extension-fingerprinting techniques [71], [44], [77], [74] to infer the presence of these extensions and ignore the affected attributes when generating the F P ID . For Brave, websites simply need to check the User-agent header.…”
Section: E Optimization Effect: Leveraging Browser Fingerprintsmentioning
confidence: 99%
“…On the other hand, using a randomized value will result in the website calculating different identifiers across visits. As such, websites can leverage extension-fingerprinting techniques [71], [44], [77], [74] to infer the presence of these extensions and ignore the affected attributes when generating the F P ID . For Brave, websites simply need to check the User-agent header.…”
Section: E Optimization Effect: Leveraging Browser Fingerprintsmentioning
confidence: 99%
“…Tian et al [51] demonstrated how the HTML5 screen-sharing API could be used for various attacks; the proposed history sniffing attack requires the target URLs to actually be rendered on the user's screen, presenting an obstacle for the practicality of the attack and limiting the number of target URLs that can be tested. Karami et al [25] showed how the Performance API can be used to detect what browser extensions a user has installed.…”
Section: Related Workmentioning
confidence: 99%
“…Starov et al [34] presented XHOUND to investigate and quantify the finger-printability of Chrome extensions through DOM-based modifications. Soroush et al [20] extended the approach by automatic generating behavioral fingerprints. Alexander et al [32] studied a class of extension revelation attacks, where extensions reveal themselves by injecting their code on web pages, and invalidated the randomized ID of Firefox, and the attacker can use the random ID as a reliable fingerprint of the users.…”
Section: Related Workmentioning
confidence: 99%